Transition metal (Co, Ni) nanoparticles wrapped with carbon and their superior catalytic activities for the reversible hydrogen storage of magnesium hydride. Issue 5 (20th January 2017) - Huang, Xu; Xiao, Xuezhang; Zhang, Wei; Fan, Xiulin; Zhang, Liuting; Cheng, Changjun; Li, Shouquan; Ge, Hongwei; Wang, Qidong; Chen, Lixin
Abstract : MgH2 doped with TM/C nanoparticles exhibits a fast kinetics with 6.5 wt% H2 from 100 to 200 °C. Carbon exists on surface of TM/C hinders the agglomeration of catalysts. Abstract : Magnesium hydride (MgH2 ) exhibits long-term stability and has recently been developed as a safe alternative to store hydrogen in the solid state, due to its high capacity of 7.6 wt% H2 and low cost compared to other metal hydrides. However, the high activation energy and poor kinetics of MgH2 lead to inadequate hydrogen storage properties, resulting in low energy efficiency. Nano-catalysis is deemed to be the most effective strategy in improving the kinetics performance of hydrogen storage materials. In this work, robust and efficient architectures of carbon-wrapped transition metal (Co/C, Ni/C) nanoparticles (8–16 nm) were prepared and used as catalysts in the MgH2 system via ball milling to improve its de/rehydrogenation kinetics. Between the two kinds of nano-catalysts, the Ni/C nanoparticles exhibit a better catalytic efficiency. MgH2 doped with 6% Ni/C (MgH2 -6%Ni/C) exhibits a peak dehydrogenation temperature of 275.7 °C, which is 142.7, 54.2 and 32.5 °C lower than that of commercial MgH2, milled MgH2 and MgH2 doped with 6% Co/C (MgH2 -6%Co/C), respectively. MgH2 doped with 6% Ni/C can release about 6.1 wt% H2 at 250 °C. More importantly, the dehydrogenated MgH2 -6%Ni/C is even able to uptake 5.0 wt% H2 at 100 °C within 20 s. Moreover, a cycling test of MgH2 doped with 8% Ni/C demonstrates its excellent hydrogen absorption/desorption stability with respect to both capacity (up to 6.5 wt%) and kinetics (within 8 min at 275 °C for dehydrogenation and within 10 s at 200 °C for rehydrogenation). Mechanistic research reveals that the in situ formed Mg2 Ni and Mg2 NiH4 nanoparticles can be regarded as advanced catalytically active species in the MgH2 -Ni/C system. Meanwhile, the carbon attached around the surface of transition metal nanoparticles can successfully inhibit the aggregation of the catalysts and achieve the steadily, prompting de/rehydrogenation during the subsequent cycling process. The intrinsic catalytic effects and the uniform distributions of Mg2 Ni and Mg2 NiH4 result in a favorable catalytic efficiency and cycling stability. Nano-catalysts with this kind of morphology can also be applied to other metal hydrides to improve their kinetics performance and cycling stability.